Association between hepatic steatosis index and impaired fasting glucose: a multicenter retrospective cohort study in China - Chen, Yimei; Han, Jieying; Zhao, Siwen; Shi, Yongjie; Jia, Hongyun; Lu, Songyao; Wu, Juan; Huang, Sicong (Frontiers in Endocrinology, 2025)
BackgroundThe Hepatic Steatosis Index (HSI) is a simple screening tool for adults with non-alcoholic fatty liver disease (NAFLD). While lipid and glucose metabolism are closely interrelated, few studies have examined the association between HSI and impaired fasting glucose (IFG). This study aims to investigate the relationship between HSI and IFG risk in a large Chinese cohort.MethodsThis retrospective cohort study analyzed health examination data collected from 2010 to 2016 across 11 cities in China by the Rich Healthcare Group. Multivariable Cox regression and restricted cubic spline (RCS) analyses were used to evaluate the association between baseline HSI and IFG. Subgroup analyses were conducted to assess the robustness of the findings.ResultsA total of 75,911 participants with a mean age of 40.9 ± 12.1 years were included, among whom 9,908 (13.1%) developed IFG. After adjusting for potential confounders, each one-unit increase in baseline HSI was associated with a 5% higher risk of IFG (HR=1.05, 95%CI). RCS analysis revealed that the increase of risk plateaued when HSI exceeded 35.31. Subgroup analyses demonstrated the stability of these findings.ConclusionElevated baseline HSI is a significant risk factor for IFG in Chinese adults. These findings highlight the potential utility of HSI in identifying individuals at risk of glucose dysregulation.